Patterns of interaction between factors that enhance or inhibit recovery from chronic low back pain. (February 2015) - Nichols, Vivien P.; Griffiths, Frances E.; Patel, Shilpa; Lamb, Sarah E.
Abstract Purpose: This interview study aimed to capture an account of change in low back pain over time and understand the interaction of known bio-psychosocial risk factors. Methods: Thirty-four participants from the Back Skills Training (BeST) UK trial, evaluating a cognitive behavioural approach intervention for LBP, gave 61 interviews. Semi-structured interviews taken once or twice post intervention explored participants' experiences of LBP and the intervention received. Initial thematic analysis of the data gave themes, which participants spoke about in an integrated way. Rereading of whole transcripts identified interactions between themes, which we classified as helpful or unhelpful to recovery. The team also explored whether there were correlations with Roland and Morris Disability Questionnaire (RMDQ) scores from the main trial. Results: Web diagrams gave a graphic representation of the interactions between factors, which were highly individual and time specific. We identified three categories of webs; dense web (mostly unhelpful), open web (helpful and unhelpful) and sparse web (mostly helpful). These categories correlated with (RMDQ) scores. Conclusions: Facilitators as well as potential barriers to recovery give added insight when considering psychosocial risk factors. Web categories highlight patterns of interaction between psychosocial factors, which underlie levels of disability. These patterns of interaction may help to guide clinicians in their choice of treatment approaches. Implications for Rehabilitation Low Back Pain LBP is common and poor outcome is more likely in the presence of psychosocial factors and co-morbidity. Interaction between these factors can be helpful and/or unhelpful, reinforcing or minimising negative or positive effects. Identifying patterns of interaction between these factors can help clinicians to choose appropriate treatment strategies to address these patterns.